2001
DOI: 10.1093/ageing/30.1.33
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacy discharge plan for hospitalized elderly patients—a randomized controlled trial

Abstract: we found no evidence to suggest that the co-ordinated hospital and community pharmacy care discharge plans in elderly patients in this study influence outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
199
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(205 citation statements)
references
References 0 publications
3
199
2
1
Order By: Relevance
“…40 Home visits by clinical pharmacists in one trial of 872 discharged patients 80 years or older, despite changes in management of 20% of participants, resulted in a 30% increase (P = 0.009) in readmissions, 41 whereas in another trial involving 362 medical patients, no impact on readmissions was noted. 42 One trial reported significantly reduced adverse drug events as a consequence of pharmacist counselling of patients following discharge but no change in readmissions. 43 Two trials involving 334 patients with chronic lung disease failed to show any impact of nurse home visits on readmissions, 44,45 in contrast to two trials involving 878 patients with cardiac disease that demonstrated a significant (P < 0.05) one-third decrease in readmissions.…”
Section: Post-discharge Home Visits or Telephonic Follow-upmentioning
confidence: 99%
“…40 Home visits by clinical pharmacists in one trial of 872 discharged patients 80 years or older, despite changes in management of 20% of participants, resulted in a 30% increase (P = 0.009) in readmissions, 41 whereas in another trial involving 362 medical patients, no impact on readmissions was noted. 42 One trial reported significantly reduced adverse drug events as a consequence of pharmacist counselling of patients following discharge but no change in readmissions. 43 Two trials involving 334 patients with chronic lung disease failed to show any impact of nurse home visits on readmissions, 44,45 in contrast to two trials involving 878 patients with cardiac disease that demonstrated a significant (P < 0.05) one-third decrease in readmissions.…”
Section: Post-discharge Home Visits or Telephonic Follow-upmentioning
confidence: 99%
“…Among evaluations conducted by means of comparison trials, there have been discrepancies, with some authors reporting higher patient satisfaction among those who received the intervention being studied than among those who received no intervention (i.e., usual care), 12,16 and other authors reporting no difference in satisfaction between those who received the pharmacy services intervention and those who received usual care. 21,22 In both of the studies in which patient satisfaction with pharmacy services was higher in the intervention group than the nonintervention group, the survey was developed specifically for the evaluation and was based on literature and the project itself. 12,16 In one of the studies in which satisfaction was not higher in the intervention group, 22 the survey used to assess patient satisfaction 23 had been developed to assess health services in general, not pharmacy services in particular.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15]18 This may be due to the variability in the types of pharmacist intervention provided, the cultural climate of the health system being studied, or many other factors. One possible reason for this is that the pharmacist plays an important role, but other team members, such as care coordinators and nurse educators, also need to be added to the patient's care team to have a more significant impact in reducing hospital readmissions.…”
Section: 10mentioning
confidence: 99%